Values for Self-Care and Sociaty to Prevent and Control the Spread of COVID-19 and the Impact of COVID-19 on Thai and Indonesia Undergraduate Students: A Case Study of Srinakharinwirot University and Tadulako University - Klaharn, Rungrudee; Tamrin, Mukrim; Chakchaichon, Chukiat; Siriyanon, Suwitchaya (Journal of The Royal Thai Army Nurses, 2023)
The objectives of this research was study self-care and social care values of Thai and Indonesian students in regard to preventing and controlling the spread of COVID-19 and the impact of the pandemic. The sample was comprised of 400 undergraduate students at Srinakharinwirot University in Thailand and Tadulako University in Indonesia, obtained by simple random sampling. The research instrument was a Google Forms questionnaire with a five-point rating scale. The content validity index was 0.67 to 1.00, and the reliability based on Cronbach’s alpha coefficient was 0.93 and 0.89. The results showed that 1) the overall self-care and social care values of the Indonesian students were at a high level (M = 3.82, S.D. = 0.16), while the Thai students were at the highest level (M = 4.39, S.D. = 0.14); 2) there was a statistically significant difference at the .05 level between the self-care and social care values of the Thai and Indonesian students; 3) the overall impact of COVID-19 on Thai and Indonesian students was at a high level: (M = 4.03, S.D. = 0.25) and (M = 3.75, S.D. = 0.15), respectively; and 4) there was a statistically significant difference at the .05 level in the impact of COVID-19 between Thai and Indonesian students. Therefore, universities should provide counseling for students to help them deal with pandemic-induced stress, as well as reduce enrollment fees or extend the payment time.